Directly acting antivirals are safe and effective in HCV positive patients aged 80 years and older: a multicenter real-life study. Issue 7 (3rd July 2021) - Pugliese, Nicola; Giorgini, Alessia; Maggi, Daniela; Capogreco, Antonio; Dibenedetto, Clara; Lubrano Lobianco, Federica; Dal Buono, Arianna; Monico, Sara; Meli, Rossella; Battezzati, Pier Maria; Lleo, Ana; De Santis, Adriano; et al.
ABSTRACT: Background : Treatment of chronic Hepatitis C with directly acting antivirals (DAAs) can bring to sustained virologic response (SVR) in approximately 95% of patients. Efficacy and safety of DAAs in aging patients has not been widely analyzed. We aimed to determine safety and efficacy of DAA-based regimens in a cohort of elderly patients in a real-life setting. Research Design and Methods : We retrospectively investigated safety and efficacy of DAAs in HCV patients of 80 years or older treated in three Hepatology Units. Results and Expert opinion : During the study period, 170 patients older than 80 years received DAAs. Their mean age was 82, 3 years. The predominant HCV genotype was 1 (100 patients, 59%). Among the 93 cirrhotic patients (54, 7%), 18 had CPT score > A5. Different DAAs regimens were used. Concomitant drugs were common: 163 patients (95, 8%) taking at least one drug. In 11 patients, usual therapy had to be changed to start antiviral treatment. Two serious adverse events occurred. Four patients terminated treatment prematurely. In total, 45 patients (26, 5%) testified mild side effects. HCV-RNA undetectability at week 12 of treatment follow-up was achieved in 168/170 patients. DAA treatment in HCV patients of 80 years or older is efficacious and safe. Drug–drug interaction should be judiciously evaluated before starting therapy.